A new hydrated crystalline form of N-[(E)-(4-hydroxyphenyl)methylidene]-1H-1,2,4-triazol-3-amine and its antifungal activity - Boualia Boutheina; Bouhidel Zakaria; Aouatef Cherouana; Bendeif El-Eulmi (Acta Crystallographica Section E: Crystallographic Communications)
The synthesis, crystal structure, Hirshfeld analysis, and antifungal assessment of a new monohydrated Schiff base with a triazole moiety are reported. The structural study revealed the presence of three significant hydrogen bonds (N—H...N, O—H...N, and O—H...O), which contribute to the cohesion of the crystal. These bonds generate two-dimensional layers parallel to the bc plane, built on the basis of rings with the graph-set motifs R44(8) and R44(24). The crystal structure is further consolidated by π–π interactions between similar rings. The antifungal activity of the Schiff base was evaluated against three fungi: Fusarium oxysporum, Botrytis cinerea, and Alternaria alternata, showing significant antifungal activity, particularly against Alternaria alternata.